2021
DOI: 10.2196/17418
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of a Mobile Phone Support Tool (Call for Life Uganda) for Promoting Adherence to Antiretroviral Therapy Among Young Adults in a Randomized Controlled Trial: Exploratory Qualitative Study

Abstract: Background Adherence to treatment is critical for successful treatment outcomes. Although factors influencing antiretroviral therapy (ART) adherence vary, young adults are less likely to adhere owing to psychosocial issues such as stigma, ART-related side effects, and a lack of access to treatment. The Call for Life Uganda (CFLU) mobile health (mHealth) tool is a mobile phone–based technology that provides text messages or interactive voice response functionalities through a web interface and offer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 29 publications
2
31
0
1
Order By: Relevance
“…Previous VDOT studies conducted in India, the United States, and Vietnam have also reported similar mixed concerns with privacy [ 24 , 25 , 39 ]. The importance of preserving confidentiality, guarding against unintended disease disclosure, and stigma also emerged as prominent themes in studies on acceptance of mobile health (mHealth) interventions among people living with HIV in rural and urban Uganda [ 26 , 30 , 45 ]. Indeed, the use of any mHealth interventions in monitoring treatment should be ethically comparable with the standard of care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous VDOT studies conducted in India, the United States, and Vietnam have also reported similar mixed concerns with privacy [ 24 , 25 , 39 ]. The importance of preserving confidentiality, guarding against unintended disease disclosure, and stigma also emerged as prominent themes in studies on acceptance of mobile health (mHealth) interventions among people living with HIV in rural and urban Uganda [ 26 , 30 , 45 ]. Indeed, the use of any mHealth interventions in monitoring treatment should be ethically comparable with the standard of care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dedde modo, com a finalidade de reduzir as taxas de abandono, favorecer a adesão e retenção ao tratamento e melhorar o cuidado das PVHIV, diferentes estratégias podem ser utilizadas pelos profissionais da saúde. Por exemplo, estudo realizado em Uganda junto a PVHIV mostrou que a utilização de mensagens de texto e ligação como meio de educação em saúde levaram a maior adesão à medicação, fortalecimento de vínculo com os profissionais e o aumento do conhecimento sobre o cuidado com a saúde 30 .…”
Section: Discussionunclassified
“…This substudy also complements our parent study that was conducted to determine the impact of IVR technology on Medical Outcomes HIV Quality of Life scores and viral suppression at 12 months, which showed better study outcomes and higher quality-of-life scores for participants with higher use of the CFLU tool than for low users [ 45 ]. It further complements another study (qualitative) by the team that explored the acceptability of a mobile phone support tool (CLFU) for promoting adherence to ART among young adults in a substudy of the RCT [ 48 ]. However, our study explored similarities and differences in the experiences, perceptions, and attitudes of people living with HIV regarding the CFLU tool among 3 categories based on the proportion of calls responded to.…”
Section: Discussionmentioning
confidence: 99%
“…At baseline, participants in the intervention arm were trained on how to initiate and receive calls, and the messages were provided in four languages: English, Luganda, Kiswahili, and Runyankore. A description of how the tool was introduced to the participants is detailed in 2 separate study publications that include the RCT study and the qualitative exploratory study findings [ 45 , 48 ]. At baseline, all patients underwent a quality-of-life assessment, which was repeated at months 6, 12, and 24.…”
Section: Methodsmentioning
confidence: 99%